2009
DOI: 10.1016/j.polsoc.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The failure of water utilities privatization: Synthesis of evidence, analysis and implications

Abstract: During much of the 1990s, water utilities worldwide experienced a wave of privatization. The rationale for this is largely based on two hypotheses: the fiscal hypothesis and the efficiency hypothesis. This article examines the evidence and concludes that water utilities privatization has been a failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 4 publications
1
46
0
2
Order By: Relevance
“…In many countries, the entrance of private actors in the water supply industry has failed to achieve the expected goals of greater efficiency and, for this reason, the involvement of the private sector in the provision of the service has been subject to increasing criticism. The large number of empirical studies conducted from across the US, Europe and developing countries that used different methodologies such as econometric or multiple case studies, provided results that are often ambiguous and contradictory, even showing that privatization does not necessarily provide better cost service delivery [10,11]. Kirkpatrik and Parker [12] even found that, in some cases the private sector participation in the water provision industry caused the cancellation of some services or an increase of water tariffs to the detriment of some consumer groups.…”
Section: Private Vs Public Ownership And/or Management Of Water Provmentioning
confidence: 99%
“…In many countries, the entrance of private actors in the water supply industry has failed to achieve the expected goals of greater efficiency and, for this reason, the involvement of the private sector in the provision of the service has been subject to increasing criticism. The large number of empirical studies conducted from across the US, Europe and developing countries that used different methodologies such as econometric or multiple case studies, provided results that are often ambiguous and contradictory, even showing that privatization does not necessarily provide better cost service delivery [10,11]. Kirkpatrik and Parker [12] even found that, in some cases the private sector participation in the water provision industry caused the cancellation of some services or an increase of water tariffs to the detriment of some consumer groups.…”
Section: Private Vs Public Ownership And/or Management Of Water Provmentioning
confidence: 99%
“…Theories of government failure have been used to explain the rather poor performance of public water utilities and irrigation agencies in many developing countries, for instance Araral (2008Araral ( , 2009). …”
mentioning
confidence: 99%
“…However, in the past water used to be referred as a free good, by which this has been replaced by new perspective that water can be treated either as social good or economic commodity (Randall, 1981;Milliman, 1959;Saleth and Dinar, 2005). First those who hold the view that water is a social good have looked into several factors including its necessity to life and perquisite of society social development (Araral, 2009;Brajer and Martin, 1990) and its association with agrarian and industrial revolution (Rose, 1990). While those who hold the view that water can be considered as an economic commodity stem from the fact that water is becoming scarce and its demand is increasing.…”
Section: Theoretical Considerationmentioning
confidence: 99%
“… Fairness (equity) by which to distribute water among shareholders (Easter et al, 1999, Dietz, 2003)  Efficiency to the extent of how to utilize water productively (Araral, 2009, Bjornlund, 2003.…”
Section: Theoretical Considerationmentioning
confidence: 99%